2004
DOI: 10.1007/s11998-004-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

Advanced techniques for nanocharacterization of polymeric coating surfaces

Abstract: Surface properties of a polymeric coating system have a strong influence on its performance and service life. However, the surface of a polymer coating may have different chemical, physical, and mechanical properties from the bulk. In order to monitor the coating property changes with environmental exposures from the early stages of degradation, nondestructive techniques with the ability to characterize surface properties with micro-to nanoscale spatial resolution are required. In this article, atomic force mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Similar results have been reported from other AFM and LSCM studies on the weathering of polymeric coatings. 22,24,25 These observations indicate that while higher magnification images are very important for visualizing physical changes occurring in the very early stage of coating degradation 23,26 , the longer wavelength surface roughness may be more directly related to the gloss measurement. More quantitative analysis can be provided by mathematical models.…”
Section: Gloss Retention and Relationship Between Optical Property Anmentioning
confidence: 96%
“…Similar results have been reported from other AFM and LSCM studies on the weathering of polymeric coatings. 22,24,25 These observations indicate that while higher magnification images are very important for visualizing physical changes occurring in the very early stage of coating degradation 23,26 , the longer wavelength surface roughness may be more directly related to the gloss measurement. More quantitative analysis can be provided by mathematical models.…”
Section: Gloss Retention and Relationship Between Optical Property Anmentioning
confidence: 96%
“…A recent study of buried interface morphologies of polymerized organics showed structures not unlike those observed in this work. 17 The mechanism of resist surface texture formation and its importance in adhesive behaviors requires further investigation. …”
Section: Adhesionmentioning
confidence: 99%
“…1 The chemical modification of polymers resulting from photooxidation would lead to changes in physical and mechanical properties, such as molecular mass, 2 crosslinking density, 3,4 glass transition temperature (T g ), 3,4 modulus and hardness, 5,6 roughness and gloss. 7,8 Extensive studies by NIST 6,[9][10][11][12] on service life prediction of polymeric materials from nanoscale to macroscale via atomic force microscopy, confocal microscopy, nanoindentation and spectroscopy, indicate that degradation of polymeric materials initiates at sub-micrometer degradation-susceptible regions on the surface, and then the degraded regions expand, deepen, and aggregate with longer exposures. The photodegradation mode of polymeric materials appears as a heterogeneous process rather than an ablation.…”
Section: Introductionmentioning
confidence: 99%